The Use Of Dubbing Video Technique For Improving Students Speaking Skill and Confidence of Senior High School Students - Indria Merdeka Wati; Yenni Rozimela (Journal of English Language Teaching, 2019)
AbstractMany students have difficulties in speaking.Lack of ideas is the main problem that students face in speaking.It is influenced by lack of mastery of vocabulary and pronouncing words. Based on these problems an appropriate teaching technique is needed to help students improve theirspeaking ability and self-confidence. This paper aims to explain how to improve students’ speaking skill by using dubbing video technique. Dubbing video is process of fill the sound of the video where the original soundtrack is turned off. There are some stages implementing video dubbing which are; active viewing, freeze framing and prediction, silent viewing, sound on and vision off activity, repetition and role play, reproduction activity, dubbing video activity, and follow-up activity. The objective of this paper is to help the students expressing their idea based on the video that they watch in order to improve their speaking skill and self-confidence